“And When He Saw the Girl Picture, His Stockings Fell Off”. Humanitarianization of Health Mobilities and Visa for Medical Treatment - Basualdo, Lourdes (2023)
This article aims to analyze certain manifestations of «humanitarianism» in the control and regulation of health mobilities in the Argentine context. At an empirical level, it investigates one of the political uses of the health visa, from the figure of «patients under medical treatment» contained in the Migration Law, based on the transcontinental mobility experience of a girl from Sub-Saharan Africa who entered Argentina in the mid-2010s under this migratory category. Through a qualitative methodology that combines participant observations and interviews developed between 2016 and 2019, the article shows the humanitarianization work through which people or groups with greater restrictions on mobility, in the framework of the reconfiguration of the “South American regime of migration and borders”, come to be produced as deserving of humanitarian treatment, as well as the tensions and conflicts experienced during the exercise of humanitarian control of mobility. It argues that, in the process of mobility for health under study, humanitarian control is configured from the articulation between the imposition and access to visa measures, the production of “callers” and certain political uses of humanitarian imagery.